2019
DOI: 10.1093/infdis/jiz649
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin (IL) 17R/IL-22R Signaling Axis Is Dispensable for Vulvovaginal Candidiasis Regardless of Estrogen Status

Abstract: Candida albicans, a ubiquitous commensal fungus that colonizes human mucosal tissues and skin, can become pathogenic, clinically manifesting most commonly as oropharyngeal candidiasis and vulvovaginal candidiasis (VVC). Studies in mice and humans convincingly show that T-helper 17 (Th17)/interleukin 17 (IL-17)–driven immunity is essential to control oral and dermal candidiasis. However, the role of the IL-17 pathway during VVC remains controversial, with conflicting reports from human data and mouse models. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 49 publications
5
29
0
Order By: Relevance
“…More importantly, human individuals bearing inborn mutations in genes coding for IL-17 pathway components, such as CARD9 or STAT3, show greatly increased morbidity of these infections. In sharp contrast, IL-17-mediated responses are dispensable for vulvovaginal candidiasis (Yano et al, 2012;Peters et al, 2019). This is in accordance with previous observations in HIV positive patients who show increased oral thrush prevalence, but no vulvovaginal or systemic candidiasis, highlighting the site-specificity of these responses to the oral cavity (Fidel, 2011).…”
Section: Anti-candida Innate Immunity At the Mucosasupporting
confidence: 90%
“…More importantly, human individuals bearing inborn mutations in genes coding for IL-17 pathway components, such as CARD9 or STAT3, show greatly increased morbidity of these infections. In sharp contrast, IL-17-mediated responses are dispensable for vulvovaginal candidiasis (Yano et al, 2012;Peters et al, 2019). This is in accordance with previous observations in HIV positive patients who show increased oral thrush prevalence, but no vulvovaginal or systemic candidiasis, highlighting the site-specificity of these responses to the oral cavity (Fidel, 2011).…”
Section: Anti-candida Innate Immunity At the Mucosasupporting
confidence: 90%
“…However, an unbiased global transcriptomic approach using RNA-seq to detect differential gene expression in the murine vagina during infection revealed a gene signature that was strongly suggestive of an IL-17 response [66]. Moreover, this gene signature was remarkably similar to that observed during oral candidiasis [87]. Administration of halofuginone, a pharmacologic inhibitor of IL-17 T-helper cell development, resulted in elevated vaginal fungal burdens during murine infection [88].…”
Section: A Controversial Role For Il-17 Signaling?mentioning
confidence: 85%
“…Because the aforementioned effects of estrogen may impair IL-17 signaling as previously reported, similar experiments using IL-17RA-/-, ACT1-/-, and IL-22-/-mice were conducted in the absence of estrogen. Regardless of estrogen administration, susceptibility to VVC was not altered in knockout compared to wild-type animals, although less consistent colonization was observed in the absence of exogenous estrogen [87]. While the precise role for IL-17 during human infection is not known, congenital or acquired immunodeficiency affecting IL-17 or Th17 cells seemingly does not predispose women to VVC [90,91].…”
Section: A Controversial Role For Il-17 Signaling?mentioning
confidence: 91%
“…Even though IL-23p19 −/− , IL-17RA −/− and IL-22 −/− mice intravaginally inoculated with Candida suggested little-to-no evidence of Th17 cytokines being primary effectors during acute inflammation [114], the role of IL-22 has been long investigated recently for its ability to provide antifungal resistance during infection at the mucosal sites by preventing epithelial cell damage [115]. Interestingly, a mouse model of VVC revealed that the role of the IL-17/IL-22 axis is independent from estrogen administration [116].…”
Section: Immunology: Rvvc As An Autoinflammatory Diseasementioning
confidence: 99%